Effect of Stretching Combined With a Slow Deep Breathing Exercise on Patients' Anxiety after Coronary Artery Bypass Grafting: A Randomized Clinical Trial - Azam Zarneshan; Naser Safaie; Leyla Esmealy; Babak Esmealy (Golestan University of Medical Sciences, 2022)
Background: Anxiety is commonly experienced by patients undergoing coronary artery bypass grafting (CABG), which is also closely related to the recovery of patients. This study aimed to determine effect of stretching combined with a slow deep breathing exercise (S+SDBE) on anxiety of patients after CABG. Methods: In this randomized clinical trial, 50 eligible patients (aged 45-65 years) were randomly divided into experimental (n=25) and control (n=25) groups. The exercise program was performed by the experimental group in the morning and afternoon for 6 days. The patients in the control group received only routine care from the hospital. The Faces Anxiety Scale was used for assessment of anxiety. Data were analyzed using non-parametric tests at a significant level of 0.05. Results: Data from 48 patients (35 males and 13 females) were analyzed. The mean age of the patients was 59.66 ± 4.1 years. The mean anxiety scores decreased significantly in the experimental group in the morning and afternoon compared with the control group (P<0.05). The anxiety scores differed significantly between the two groups in the morning of days 5 (P=0.025, effect size d=0.32) and 6 (P=0.017, effect size d=0.34) and in the afternoon of days 4 (P<0.001, effect size d=0.51), 5 (P<<0.001, effect size d=0.53), and 6 (P<<0.001, effect size d=0.61). Conclusion: Based on the results,S+SDBE can be applied to decrease patients' anxiety after CABG.